Information aggregation in Poisson-elections - Mehmet Ekmekci; Stephan Lauermann (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
The modern Condorcet jury theorem states that under weak conditions, when voters have common interests, elections will aggregate information when the population is large, in any equilibrium. Here, we study the performance of large elections with population uncertainty. We find that the modern Condorcet jury theorem holds if and only if the expected number of voters is independent of the state. If the expected number of voters depends on the state, then additional equilibria exist in which information is not aggregated. The main driving force is that, everything else equal, voters are more likely to be pivotal if the population is small.
Keywords: 330; Wahl; Abstimmungsregel; Informationsverhalten; Aggregation; Abstimmungsspiel; Diskrete Verteilung; Theorie